MEMBANGUN MENTAL TECHNOPRENEURSIP DALAM UPAYA MENINGKATKAN EKONOMI KREATIF PADA MAHASISWA PSDKU UNTAD MOROWALI - Teguh Hilmansyah; Erwan Sastrawan Farid; Mohammad Amin; Ririen Hardani (Jurnal Abdimas Bina Bangsa, 2023)
Building a technopreneur mentality has a significant positive impact. Students who have technopreneur spirit and skills have the potential to create more technology startups and creative businesses. The Community Service (PkM) activity was carried out with two methods, namely knowledge transfer and the Community Development Model. The event was attended by 20 students from three study programs at PSDKU UNTAD Morowali and took place with direct interaction in Bungku city. The results of this PkM hope that PSDKU UNTAD Morowali students will be able to become competitive drivers of change in the world of industry and the creative economy. The evaluation showed that the average score of participants in the pre-test was 65.6, still below the standard of 75. However, after the presentation of the material, the average score of participants in the post-test increased to 82.4, indicating an increase in participants' understanding after participating in the PkM. In the future, this activity should involve technopreneurship practitioners from various fields